LANGUAGE EDUCATION AND LANGUAGE SKILLS DEVELOPMENT - Rustamov Ilkhom Tursunovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article discusses important aspects of teaching a foreign language. In particular, the issue of teaching a foreign language subject by the formation of speech and language competencies is covered. Also, in the formation of these competencies, effective technologies are presented that are considered optimal.